Motor axonal excitability properties are strong predictors for survival in amyotrophic lateral sclerosis. Issue 7 (7th May 2012) - Kanai, Kazuaki; Shibuya, Kazumoto; Sato, Yasunori; Misawa, Sonoko; Nasu, Saiko; Sekiguchi, Yukari; Mitsuma, Satsuki; Isose, Sagiri; Fujimaki, Yumi; Ohmori, Shigeki; Koga, Shunsuke; Kuwabara, Satoshi
Abstract : Objective: The aim of this study was to investigate whether axonal excitability indices are associated with survival in patients with amyotrophic lateral sclerosis (ALS). Previous nerve excitability studies suggested increased persistent sodium currents in motor axons of patients with ALS, which lead to axonal hyperexcitability and potentially enhance neuronal death. Methods: 112 patients with sporadic ALS were followed up until endpoint (death or tracheostomy). Multivariate analyses were performed using the Cox proportional hazard model. Threshold tracking was used to measure multiple axonal excitability indices in median motor axons, such as strength–duration time constant (SDTC; a measure of nodal persistent sodium current). Latent addition was also used to estimate the magnitude of persistent sodium currents. Results: The overall median tracheostomy-free survival from onset was 37 months. Prolonged SDTC was strongly associated with shorter survival (adjusted HR 4.07; 95% CI 1.7 to 9.8; p=0.0018) compared with older onset age (>60 years; HR=1.80) and bulbar onset (HR=1.80). Estimated median survival was 34 months in the longer SDTC group and 51 months in the shorter SDTC group. This index was highly statistically significant even after multiple testing adjustments with age and site of onset (bulbar or limb). Latent addition study results were consistent with these findings. Conclusions: Axonal persistent sodium currents, estimated by SDTC and latent addition, are strong and independent predictors for shorter survival in patients with ALS. Membrane hyperexcitability is possibly associated with motor neuronal death, and modulation of excessive sodium currents could be a novel therapeutic option for ALS.